Problems of development of project management in the system of public administration of the Republic of Kazakhstan - Мухтарова, К.; Аширбекова, Л.; Жакупбекова, Г. (Journal of Economic Research & Business Administration, 2018)
This article discusses the need and prerequisites for the introduction of a project management system in state authorities. The relevance of project management is due to new challenges to the system of public administration in the Republic of Kazakhstan. In the contemporary conditions, the importance of the ability of state bodies to implement the planned projects on time and within the framework of the budgeted budgets is increased. It is also necessary to distinguish project activities from the overall activities of the organization. For this purpose, the article identifies the similarities between the process and project activities, identifies the main advantages from the implementation of the project approach in public administration, examined the status and main directions for the promotion of project management in public administration in the Republic of Kazakhstan. The international experience of project management is considered and on the basis of them the ways of development of the project approach in the public sector of Kazakhstan.